2014
DOI: 10.3844/ajmsp.2014.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical and Mass Spectral Assessment Methods for Identification of Some Contagious Mastitis Pathogens

Abstract: Mastitis is one of the most economic disease affecting dairy cows worldwide. Identification of mastitis pathogens still depends principally on culture and phenotypical method, which is a difficult and timeconsuming. Newly, microbiologists have focused their attention on the use of Mass Spectrometry (MS) for microbial identification, especially Matrix Assisted Laser Desorption Ionization Time-Of-Flight (MALDI-TOF). Therefore, this study was designated to evaluate the ability of MALDI-TOF to identify some contag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Because the ID32 STAPH system is normally used as a reference approach, results attained with ID32 STAPH are added. In the study of El Behiry et al (2014), 89% of the tested S. aureus strains were correctly identified via the ID32 STAPH system, which matched our study, in which the ID32 STAPH system was able to correctly identify (84%) (in all tests) the Staphylococcal species.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Because the ID32 STAPH system is normally used as a reference approach, results attained with ID32 STAPH are added. In the study of El Behiry et al (2014), 89% of the tested S. aureus strains were correctly identified via the ID32 STAPH system, which matched our study, in which the ID32 STAPH system was able to correctly identify (84%) (in all tests) the Staphylococcal species.…”
Section: Discussionsupporting
confidence: 84%
“…PMFT is one of powerful, fast, truthful, and correct technique of identifying microorganisms, especially in subclinical and clinical cases of mastitis (Carbonnelle et al, 2007;El Behiry et al, 2014;Elbehiry et al, 2016). The application of PMFT in the diagnosis of mastitis has been demonstrated by Nonnemann et al (2018); it was shown to be a cost-effective and quick method when applied to 500 isolates, and twentyfour genera and sixty-one specifies were identified.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI‐TOF‐MS therefore, represents one of the major, fast and correct tool for identification and typing of various microorganisms isolated from clinical and subclinical samples (Carbonnelle et al., ; El Behiry et al., ; Singhal et al., ). In our study, detection and typing of S. aureus and CNS strains were carried out by proteomic analysis and the frequency of precise identification at the genus and species levels was 194/198 (97.97%) and 44/44 (100%), respectively, with the score level ranging from 2,000 to 3,000 Da.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine mastitis remains one of the most important complications among dairy farms all over the world from the diagnostic, economic, and public health related perspective (Benić et al, ; El Behiry et al., ; Preethirani et al, ). Several cases of mastitis in cattle are caused mainly by different types of bacteria, and the species of Staphylococcus aureus ( S. aureus ) and coagulase‐negative staphylococci (CNS) are considered the most common and important bacteria that cause mastitis, both subclinical and clinical form of mastitis among dairy farms (Cabral et al., ; Haveri, ; Vasudevan et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation